Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1136/adc.86.3.215
|View full text |Cite
|
Sign up to set email alerts
|

Investigation for complement deficiency following meningococcal disease

Abstract: Background and aims: The incidence of complement abnormalities in the UK is not known. It is suggested in at least three major paediatric textbooks to test for abnormalities of the complement system following meningococcal disease (MCD). Methods: Over a four year period, surviving children with a diagnosis of MCD had complement activity assessed. A total of 297 children, aged 2 months to 16 years were screened. Results: All children except one had disease caused by B or C serogroups. One child, with group B me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 8 publications
0
20
0
Order By: Relevance
“…A relatively high frequency of C6 deficiency has been detected in the western Cape population of South Africa (330,358). The association of complement deficiencies with invasive neisserial infections prompted several studies to estimate the frequency of complement deficiencies among patients with their first episode of systemic neisserial infection (24,80,94,109,111,114,134,192,247,313,321,351,363,393). Figueroa and Densen (128) plotted the incidence of complement deficiency detected in patients with meningococcal disease versus the incidence of meningococcal disease in the general population and showed that the rate of complement deficiencies detected dropped in areas where the incidence of disease was high.…”
Section: Frequency Of Hereditary Complement Deficiencies Among Patienmentioning
confidence: 99%
“…A relatively high frequency of C6 deficiency has been detected in the western Cape population of South Africa (330,358). The association of complement deficiencies with invasive neisserial infections prompted several studies to estimate the frequency of complement deficiencies among patients with their first episode of systemic neisserial infection (24,80,94,109,111,114,134,192,247,313,321,351,363,393). Figueroa and Densen (128) plotted the incidence of complement deficiency detected in patients with meningococcal disease versus the incidence of meningococcal disease in the general population and showed that the rate of complement deficiencies detected dropped in areas where the incidence of disease was high.…”
Section: Frequency Of Hereditary Complement Deficiencies Among Patienmentioning
confidence: 99%
“…The high number of cases with CD seen in the first series may have been influenced by the low incidence of MCD in their population, as a greater proportion of children with CD would be expected in such areas [8]. In contrast, results from a country of high MCD incidence only revealed one case of complement deficiency in 297 cases of MCD [10].…”
Section: Discussionmentioning
confidence: 78%
“…Routine screening for complement deficiency in children with one episode of meningococcal disease is not supported by existing data from northern European children if caused by the serotypes most prevalent in that population; only one of 296 children investigated in the United Kingdom with group B or C infection was found to have a complement deficiency and that child had a history of recurrent invasive infection with encapsulated organisms [41]. However, if a less common Neisseria meningitidis serotype (such as W135 or Y in the United Kingdom) is isolated or there is recurrent infection or a family history of meningococcal disease, further investigation is warranted.…”
Section: Warning Signs For Microbiologists/infectious Diseases Physicmentioning
confidence: 90%